Transformasi Peranan Aktor Dalam Virtual Movement (Studi Kasus Petisi #sayaKPK melalui change.org) - Sih Natalia Sukmi (PAX HUMANA, 2015)
New media provide opportunities of new interaction patterns in raising collective action. This study seeks to explain how actors play a role in the movement of the virtual movement to create the success of the movement. Actor Network Theory Perspective be used as a paradigm of thinking. The method used is qualitative case study #sayaKPK uploaded petition through change.org. Results of the study revealed that ANT applied in such cases. This perspective suggests that the actor who plays the movement is not only meant as a human being, but also material and texts are interconnected in a network that hyperconnected. Keywords: Virtual, Movement, ANT